Պատմական անտիպ վկայութիւն Աւետիք Եւդոկիացի պատրիարքի մասին - Մինասեան, Միհրան
This article presents a poem written in the 1710s concerning some turbulent ecclesiastical developments inside the Constantinople Armenian community. It is an important source and contains valuable details about the historical events of that period. The protagonist of the work is the Armenian Patriarch of Constantinople Avetik‘ Evtokiats‘i (1657-1711), a staunch opponent of the Catholic propaganda. Charles Ferriol, the French ambassador to the Ottoman Empire, in collaboration with several Armenian Catholics and Jesuits, kidnapped the patriarch and took him to France, where after six years of detention in various prisons he was forced to convert to Catholicism; later he was released from prison and soon died. Many researchers identify Avetik‘ Evdokats‘i as the so-called “Man in the Iron Mask.” The fact of the abduction of Patriarch Avetik‘ is exceptional in its kind and has no analogues in the church history. В данной статье впервые представлена поэма 10-х гг. XVIII века, посвященный бурным церковным процессам в Константинопольской армянской общине. Это важный источник, содержащий ценные подробности об исторических событиях указанного периода. Главным действующим лицом поэмы является константинопольский армянский патриарх Аветик Евдокаци (1657-1711), ярый противник католической пропаганды в армянской церковной среде. Французский посол в Османской империи Шарль Фериоль, в сотрудничестве с несколькими армянамикатоликами и иезуитами, похитил патриарха и вывез во Францию, где он, после шестилетнего содержания в различных тюрьмах, под принуждением перешел в католичество, затем освободился из заключения и вскоре умер. Многие исследователи отождествляют Аветика Евдокаци с так называемым “Человеком в железной маске”. Факт похищения патриарха – своего рода исключение, не имеющее аналогов в истории церкви.
Keywords: Կաթոլիկ քարոզչութիւն; Կ.Պոլսոյ հայոց Պատրիարքութիւն; Եկեղեցու գործիչներ